A Macedonian Perspective on the Migration Crisis - Spasov, Aleksandar Lj. (Clingendael Institute, 2016)
The refugee/migrant crisis of 2015 and its aftermath in 2016 isn’t a ‘typical’ refugee crisis. The development of the crisis leads to the conclusion that Europe and the world face a phenomenon of refugee migration or movement of peoples unprecedented in recent history. In this definition of the crisis, not just the numbers have played a role. Although most of the people were indeed trying to escape war, unlike ‘usual’ refugees finding a ‘safe harbour’ in the first safe country, it wasn’t their final goal. Most of them embarked on a long journey through several south-eastern European countries, determined to reach the ‘desired destination for a better life’, and in almost all cases these were western European countries, especially Germany. Furthermore, alongside refugees fleeing from war, there were many refugees fleeing from extreme poverty, insurgency or long-lasting instability. Finally, Europe, or more precisely the European Union, failed to adequately address the crisis, both in their definition of the crisis (a refugee issue, mass migration or a mixed phenomenon) and in terms of effective and functioning common European asylum policies.
Keywords: EU, Migration Crisis, Macedonia